Determination of the structural and functional impact of high-risk missense SNPs in the obesity-associated gene, beta-catenin-like protein 1 (CTNNBL1), by bioinformatic methods - Avsar , Orcun (Progress in Nutrition, 2022)
Summary. Obesity with a complex etiology is significantly correlated with mortality and morbidity and it is becoming an epidemic through the worldwide. Moreover, obesity is a great risk factor for various diseases such as cancer, diabetes, and chronic diseases. CTNNBL1 protein belongs to armadillocontaining protein family and is a member of the spliceosome of pre-mRNA processing factor 19 (Prp19) through the interaction with N-terminal sequence of CDC5L. It has been reported that beta-catenin-like protein 1 is associated with body fat mass and Body Mass Index (BMI). The underlying molecular mechanisms of obesity is needed to be clarified by comprehensive studies. Therefore, we aimed to conduct an in silico study to identify the effects of the high-risk nsSNPs of obesity-associated CTNNBL1 gene. Deleterious missense SNPs were analyzed through five different bioinformatic tools. Only eight missense SNPs were found to be deleterious and further investigated for prediction their effects on protein stability, the evolutionary dynamics of the changes of amino acids, PTMs sites, and structure conformation. Based on the web-based bioinformatic tools, we demonstrated that only five nsSNPs R323W (rs141919968), R73Q (rs144576870), R458H (rs151227978), P274H (rs200219582), and N299S (rs369990971) from eight CTNNBL1 deleterious nsSNPs were significant. No study conducted with these deleterious nsSNPs is reported in the literature. We suppose that the predicted pathogenic nsSNPs may be implicated in the pathogenesis of obesity and confirmation of the results by population studies are required.